Like this presentation? Why not share!

# Angle between 2 lines

## on May 10, 2011

• 18,702 views

Describes how to find the angle between 2 lines

Describes how to find the angle between 2 lines

### Views

Total Views
18,702
Views on SlideShare
18,702
Embed Views
0

Likes
1
102
1

No embeds

### Report content

11 of 1 previous next

• Comment goes here.
Are you sure you want to
• (slide26) -7/4 or -7/3 -_-'
Are you sure you want to
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n

## Angle between 2 linesPresentation Transcript

• Angle between 2 LinesPreliminary Extension MathematicsDate: Tuesday 10th May 2011
• Angle between 2 lines y line l1 has gradient m1 l2 l1 line l2 has gradient m2 ∴ m1 = tan α and m2 = tan β θ α β x 0
• Angle between 2 lines y line l1 has gradient m1 l2 l1 line l2 has gradient m2 ∴ m1 = tan α and m2 = tan β θ α β x and α +θ =β (Why?) 0
• Angle between 2 lines y line l1 has gradient m1 l2 l1 line l2 has gradient m2 ∴ m1 = tan α and m2 = tan β θ and α +θ =β α β x (Exterior angle of V) 0
• Angle between 2 lines y So l2 l1 θ = β −α θ α β x 0
• Angle between 2 lines y So l2 l1 θ = β −α ∴ tan θ = tan(β − α ) θ α β x 0
• Angle between 2 lines y So l2 l1 θ = β −α ∴ tan θ = tan(β − α ) θ tan β − tan α = α β 1 + tan β tan α x 0 You will learn this formula later
• Angle between 2 lines y So l2 l1 θ = β −α ∴ tan θ = tan(β − α ) θ tan β − tan α = α β 1 + tan β tan α x 0 m1 − m2 = 1 + m1m2 Why?
• Angle between 2 lines y So l2 l1 θ = β −α ∴ tan θ = tan(β − α ) θ tan β − tan α = α β 1 + tan β tan α x 0 m1 − m2 = 1 + m1m2 When tan θ is positive, θ is acute. When tan θ is negative, θ is obtuse.
• Angle between 2 lines y Thus for two lines of gradient l2 l1 m1 and m2 the acute angle between them is given by θ m1 − m2 tan θ = α β x 1 + m1m2 0 Note that m1m2 ≠ −1 what does this mean?
• Angle between 2 lines y Thus for two lines of gradient l2 l1 m1 and m2 the acute angle between them is given by θ m1 − m2 tan θ = α β x 1 + m1m2 0 Note that m1m2 ≠ −1 the formula does not work for perpendicular lines
• Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree)
• Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3
• Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2
• Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2 2+3 ∴ tan θ = 1− 6
• Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2 2+3 ∴ tan θ = 1− 6 ∴ tan θ = −1
• Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2 2+3 ∴ tan θ = 1− 6 ∴ tan θ = −1 ∴ tan θ = 1
• Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2 2+3 ∴ tan θ = 1− 6 ∴ tan θ = −1 ∴ tan θ = 1 → θ = 45°
• Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0
• Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0∴2y = 3x + 7
• Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0∴2y = 3x + 7 3 7∴y = x + 2 2
• Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0∴2y = 3x + 7 3 7∴y = x + 2 2 3∴ m1 = 2
• Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0∴2y = 3x + 7 similarly ∴2y = −4x + 3 3 7∴y = x + 3 2 2 ∴ y = −2x + 2 3∴ m1 = ∴ m2 = −2 2
• Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0applying the formula m1 − m2 tan θ = 3 1 + m1m2 m1 = m2 = −2 2
• Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0applying the formula m1 − m2 tan θ = 3 1 + m1m2 m1 = m2 = −2 2 3 +2 ∴ tan θ = 2 1− 3
• Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0applying the formula m1 − m2 tan θ = 3 1 + m1m2 m1 = m2 = −2 2 3 +2 ∴ tan θ = 2 1− 3 −7 ∴ tan θ = 4
• Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0applying the formula m1 − m2 tan θ = 3 1 + m1m2 m1 = m2 = −2 2 3 +2 ∴ tan θ = 2 1− 3 −7 7 ∴ tan θ = ∴ tan θ = → θ = 60° 4 4
• Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree)
• Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) y = −3x + 5 y y= x+3 θ α β x 0
• Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) m1 = 1 → α = 45° y = −3x + 5 y y= x+3 θ α β x 0
• Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) m1 = 1 → α = 45° y = −3x + 5 y y= x+3 m2 = −3 → β = 108° θ α β x 0
• Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) m1 = 1 → α = 45° y = −3x + 5 y y= x+3 m2 = −3 → β = 108° But α +θ =β θ α β x 0
• Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) m1 = 1 → α = 45° y = −3x + 5 y y= x+3 m2 = −3 → β = 108° But α +θ =β θ ∴θ = 63° α β x 0